Crime of violence by children (case study of child crime in Palopo City) - Adinda Prasta Rahmadani (Central Research Institute for Agriculture (CeRIA), 2023)
The main problem discussed in this research is action crimes committed by children in Palopo City, how criminal acts are treated by children and how Islamic law treats criminal acts by children. This type of research is empirical, namely direct research in the field to obtain data and information, then analyzed using descriptive analysis methods, meaning explaining and describing problems related to drug abuse among young children in Palopo City. The approach used in this research is Sociological Juridical. The aim of the research is as follows: To find out the causes of acts of violence committed by children in the city of Palopo and to find out solutions and efforts for legal treatment against criminal acts committed by children in the City of Palopo. The problem of child delinquency in Palopo City leading to crimes occurring Criminal violence by children is quite worrying. Judging from the data obtained by the author in the field over a period of three years from 2017 to 2019, cases of children who commit unstable violent crimes sometimes increase and sometimes the number decreases, such as in 2017 there were 21 cases, then this number decreased in 2018, namely with only 6 cases, and increased slightly in 2019 with 14 cases. So the total number of cases is 41 cases from data obtained by the author at the Palopo Police.